PENGARUH KINERJA KEUANGAN PEMERINTAH DAERAH DAN HASIL PEMERIKSAAN BPK RI TERHADAP KESEJAHTERAAN MASYARAKAT Studi pada Kabupaten dan Kota di Wilayah Provinsi Jawa Timur Tahun 2013–2015 - Alam, Kenzarah Zhetira (Jurnal Ilmiah Mahasiswa FEB, 2017)
The objective of this research is to identify the effect of the local government’s financial performance and the Indonesian Supreme Audit Board’s audit report on the society’s welfare. The financial performance is measured by means of such financial ratios as fiscal decentralization degree, independence ratio, and effectiveness ratio of the local own-source revenue. The Board’s audit report is determined by the local government’s compliance with the law. Meanwhile, the society’s welfare is based on the human development index. Hence, the independent variables of the research consist of the fiscal decentralization degree, independence ratio, effectiveness ratio of the local own-source revenue, and the Board’s audit report.This quantitative study applies panel data regression method with the Common Effect Model. Due to the homegenity of financial source management system implemented in all regencies and cities in Indonesia, this research takes only 35 regencies and cities in East Java Province as the samples, with the time span between 2013-2015 fiscal year, bringing about 105 documents to be observed. The result of analysis shows that the financial performance as indicated by the fiscal decentralization degree and independence ratio positively influence the society’s welfare; on the contrary, the effectiveness ratio of the local own-source revenue and the Board’s audit report have zero influence toward the sociaty’s welfare.Keywords: Local Government’s Financial Performance; Audit Report; Human Development Index; Society’s Welfare.